Potential of baicalein in the prevention and treatment of cancer: A scientometric analyses based review. (November 2021) - Verma, Elika; Kumar, Aviral; Devi Daimary, Uzini; Parama, Dey; Girisa, Sosmitha; Sethi, Gautam; Kunnumakkara, Ajaikumar B.
Graphical abstract: Highlights: Baicalein, a pleiotropic agent, isolated from the roots of Scutelleria baicaleinsis . Scientometric analysis reveals historical and recent trends in baicalein's research. Studies have reported the immense potential of baicalein against various cancers. It modulates PI3K/AKT/mTOR, Wnt/β-catenin, MAPK, NF-κB, Notch, ROS, and Shh signalling. Further studies are warranted to establish baicalein as a promising anti-cancer agent. Abstract: Cancer is one of the deadliest diseases worldwide which kills approximately 10 million people annually. Although, substantial improvements have been made in the treatment modalities of this disease, radio-resistance, chemo-resistance, and adverse side-effects limit their potential. It is now well-established that natural products provide a less toxic and efficacious alternative in developing drugs for the treatment of cancer. Hence, we investigated the potential of baicalein, a natural compound isolated from the roots of Scutelleria baicaleinsis, which targets wide spectrum of molecular alterations involved in the progression of cancer . At the molecular level, this compound has shown to exhibit anti-inflammatory and anti-cancerous properties via modulation of multiple cell signaling pathways and transcription factors, including PI3K/Akt/mTOR, Wnt/β-catenin, MAPK, NF-κB, Smad4, Notch 1/Hes, Nrf2/Keap 1, AMPK, Src/Id1, ROS signaling, miR 183/ezrin, and Shh signaling pathways. Overall, this review provides a strong evidence for the potential of baicalein as a therapeutic agent for the treatment of different malignancies.